INCREASING CAPACITY OF WOMEN AND CADRES TO PREVENT GESTATIONAL DIABETES AND STUNTING AT POSYANDU TERATAI 8 TANGERANG - Sukarno, Anita; Azteria, Veza (Universitas Padjadjaran, 2025)
Stunting and gestational diabetes are critical health issues that need to be addressed among pregnant women and children. The impact of stunting extends beyond the present, affecting the future of children as the younger generation, both in terms of growth and cognitive development, which influences their academic achievements. It is essential to prevent nutritional deficiencies or excesses to address these issues effectively. This initiative aims to empower women of reproductive age and the Posyandu Teratai cadres in Teluknaga Village, Tangerang Regency, in preventing stunting and gestational diabetes. The methods used include health education programs on stunting and gestational diabetes, the Specific, Measurable, Achievable, Rational, and Time (SMART) Self-Homecare method as a guideline for pregnancy preparation, health maintenance during pregnancy, and postnatal care, as well as training on stunting anthropometry and blood glucose and hemoglobin measurements for the cadres. The results of this program showed a significant increase in knowledge among women of reproductive age regarding stunting, gestational diabetes, and the SMART Self-Homecare method (p<0.001), and a 100% improvement in the cadres' skills in using stunting anthropometry tools and blood glucose and hemoglobin measuring instruments. The conclusion of this program is that health education and training programs for cadres and women of reproductive age can assist healthcare workers in enhancing the knowledge and skills of the target groups, contributing to the prevention of stunting and gestational diabetes. Stunting dan diabetes gestasional menjadi masalah kesehatan yang penting untuk ditangani pada ibu hamil dan anak. Dampak stunting tidak hanya pada masa ini, namun mempengaruhi masa depan anak sebagai generasi muda, baik dari aspek pertumbuhan maupun aspek kognitif dalam pencapaian prestasinya. Faktor nutrisi yang kurang dari kebutuhan atau berlebih dari kebutuhan harus dicegah untuk mengatasi masalah tersebut. Tujuan kegiatan ini adalah untuk memberdayakan wanita usia subur dan kader Posyandu Teratai Desa Teluknaga Kabupaten Tangerang dalam pencegahan stunting dan diabetes gestasional. Adapun metode yang digunakan adalah program pendidikan kesehatan mengenai stunting dan diabetes gestasional, metode Specific Measurable Achievable Rational and Time (SMART) Self-Homecare sebagai acuan dalam persiapan kehamilan, pemeliharaan kesehatan saat hamil, dan saat bayi dilahirkan, serta pelatihan antropometri stunting dan pengukuran gula darah dan hemoglobin pada kader. Hasil dari program ini adalah terdapat peningkatan pengetahuan yang signifikan pada wanita usia subur tentang stunting, diabetes gestasional, dan mengenal metode SMART Self-Homecare (p< 0.001) dan terdapat 100% peningkatan keterampilan kader dalam penggunaan antropometri stunting dan alat ukur gula darah dan hemoglobin. Kesimpulan program ini adalah bahwa pendidikan kesehatan dan pelatihan pada kader dan wanita usia subur dapat membantu tenaga kesehatan untuk meningkatkan pengetahuan dan keterampilan sasaran sebagai upaya pencegahan stunting dan diabetes gestasional.